The Role of Artificial Intelligence Literacy and Learning Motivation in Enhancing Students' Critical Thinking Skills - elfrida Haryati par; Emirensiana Adha; Agustina Butar-Butar (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2026)
Critical thinking is an essential skill that students must possess in order to keep pace with technological developments in the digital age. However, many students still have only limited critical thinking skills. This situation is influenced by various factors, such as knowledge of artificial intelligence and motivation to learn, which have not yet been sufficiently fostered in the learning process. The objective of this study is to analyze the influence of AI competencies and learning motivation on the critical thinking skills of business students at Nusa Cendana. The study employs a quantitative method, specifically multiple linear regression. The study sample consisted of 210 respondents, determined using the Solvin formula. Data collection was conducted by distributing a questionnaire whose validity and reliability had been previously tested. The study results show that AI competencies have a positive and significant influence on students’ critical thinking skills (p < 0.05), as does learning motivation, which also has a positive and significant influence (p < 0.05). At the same time, these two variables significantly influence critical thinking skills and explain 73.3% of the variance, while the remaining 26.7% is unexplained.